Korelasi Kadar Hba1c dengan Kadar Kreatinin dan Ureum pada Pasien Diabetes Mellitus di Poliklinik Penyakit Dalam RSUD Karangasem - SRI MASYENI; NYOMAN NGURAH PRIZKY ANGGRINA; DESAK PUTU CITRA UDIYANI (Universitas Hang Tuah, 2022)
Diabetes mellitus (DM) is one of the global health problems due to the increasing number of cases. Various complications can arise due to uncontrolled blood glucose levels. The patients have a tendency to suffer from nephropathy 17 times greater than non-diabetic people, which is characterized by increased levels of creatinine and urea in the blood. The purpose of this research is to know the relationship between HbA1c levels with the levels of creatinine and urea among diabetic patients in the Internal Medicine Clinics Karangasem Hospital. This research is analytics research with a cross-sectional study design using secondary data from medical records. A total of 107 respondents enrolled in the study by consecutive sampling method. The results of this research are obtained by the level of HbA1c, creatinine, and urea in a row – which is 9.52% (SD±2,53); 1.05 mg/dL (SD ±0,67); 39.60 mg/dL (SD ± 19,72). The results of the Spearman correlation test are not significantly found between HbA1c levels with the levels of creatinine (r = -0,215, p = 0.026) and urea (r = -0,254, p = 0.008) in diabetic patients in Internal Medicine Clinics Karangasem Hospital.